Efektivitas Layanan Konseling Sebaya untuk Meningkatkan Kepercayaan Diri dan Penerimaan Diri Santri Putri Korban Bullying - A'yun, Qurrota; Fadilah, Risydah; Hardjo, Suryani (Universitas Muhammadiyah Metro, 2025)
This study aims to examine the effectiveness of peer counseling services in improving self-confidence and self-acceptance among female students who are victims of bullying in Islamic boarding schools. This research applied a one-group pretest-posttest pre-experimental design with 15 participants selected using purposive sampling. The intervention consisted of six consecutive sessions of peer counseling. Research instruments included a validated self-confidence scale and a self-acceptance scale. The data analysis using paired sample t-test showed significant increases in both self-confidence (p = 0.017) and self-acceptance (p = 0.002) after the peer counseling intervention. The findings indicate that peer counseling is an effective intervention to enhance the psychological well-being of bullied female students in Islamic boarding schools.